Teaching in higher education: organic methodologies. Issue 2 (4th March 2022) - Larsen, Ann Sofi; Johannesen, Nina; Ulla, Bente; Sandvik, Ninni
ABSTRACT: In this paper, we use process philosophy to address the increased feeling of alienation and resignation among students and teachers in Norwegian academia. By trusting the generative forces of childhood, as Deleuze and Guattari suggest, we explore changemaking potentialities in what we label 'organic methodologies' in higher education. Our question is as follows: What educational potentialities might evolve if we educationalised 'Babette's Feast' as a collective explorative act of feminist resistance in the academic system? As a starting point, we briefly present the short story Babette's Feast, written by the Danish author Karen Blixen. We experimentally educationalise the imaginary of Babette's feast and transform it into a contemporary feminist feast, facilitated through our master's program Toddler Science (0–3 years). After a brief presentation of some elements in the feminist feast, we point to processual tendencies within the feast, using Manning's logics of major/minor gestures and Massumi's concept of the trans-individual.